2011
DOI: 10.3382/ps.2010-01180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidant inclusion and oil quality on broiler performance, meat quality, and lipid oxidation

Abstract: The objective of the present study was to evaluate the effect of antioxidant inclusion and oil quality on broiler performance, meat quality, shelf life, and tissue oxidative status. Ross 308 male broilers were allotted to a randomized complete block design in a 2 × 2 factorial arrangement. Factors consisted of antioxidant (ethoxyquin and propyl gallate) inclusion at 2 levels (0 or 135 mg/kg) and oil quality (fresh soybean oil, control diet peroxide value <1 mEq/kg, or oxidized soybean oil, diet peroxide value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 27 publications
9
85
1
2
Order By: Relevance
“…When stress is more severe, the pro-oxidant systems outbalance the anti-oxidant systems, potentially producing oxidative damage to lipids, proteins, carbohydrates, and nucleic acids, ultimately leading to cell death in severe oxidative stress. Such uncontrolled oxidative reactions can lead to damage of cellular tissues and can lead to cell death, severe oxidative stress and metabolic diseases (Surai, 2000;Tavarez et al, 2011). Therefore, controlling auto-oxidation is very important to maintain feed and food quality and to enhance bird health and welfare.…”
Section: Oxidation and Free Radicals (Fr) Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…When stress is more severe, the pro-oxidant systems outbalance the anti-oxidant systems, potentially producing oxidative damage to lipids, proteins, carbohydrates, and nucleic acids, ultimately leading to cell death in severe oxidative stress. Such uncontrolled oxidative reactions can lead to damage of cellular tissues and can lead to cell death, severe oxidative stress and metabolic diseases (Surai, 2000;Tavarez et al, 2011). Therefore, controlling auto-oxidation is very important to maintain feed and food quality and to enhance bird health and welfare.…”
Section: Oxidation and Free Radicals (Fr) Formationmentioning
confidence: 99%
“…Non enzymatic antioxidants defense systems include molecules (e. g., glutathione, vitamin A and E, and carotenoids) and other elements such as selenium. When the ROS surpasses the ability of the antioxidant systems, lipid peroxidation is accelerated and accumulation of ROS is increased in serum and tissues which may damage biological membranes leading to cellular injury and dysfunctions and thus reduces productivity and suffers from diseases (Engberg et al, 1996;Halliwell and Gutteridge, 1999;Sahin and Kucuk, 2003;Tavarez et al, 2011). The tissue status of endogenous antioxidant enzymes are considered as markers for evaluating oxidative stress (Surai, 2003;Panda et al, 2008a).…”
Section: What Is Oxidative Stress?mentioning
confidence: 99%
“…Supplementation of vitamin E and rosemary powder for broiler chickens increased the oxidative stability of fats in meat measured in terms of the MDA content (Marcinčák et al, 2005). Similarly, dietary α-tocopherol supplementation reduced the TBARS content, lipid oxidation, rancid odor and flavor in raw, cooked and stored meat (Maraschiello et al, 1999;Grau et al, 2001;Ruiz et al, 2001;Tavarez et al, 2010;Taulescu et al, 2011). Taulescu et al (2011) further observed an increased concentration of α-tocopherol in meat due to supplementation with vitamin E or vitamin E with Se, which implies an enriched antioxidant status of the meat for benefits in human nutrition.…”
Section: Postmortem Efficacy In Livestockmentioning
confidence: 99%
“…Though low inclusion dose was suggested as a possible cause for the observed tenuous antioxidant effect. In a study evaluating synthetic antioxidants, EQ and propyl gallate decreased liver thiobarbituric acid reactive substances (TBARS) levels when broilers were fed diet containing oxidized oil (Tavarez et al, 2010).…”
Section: Poultrymentioning
confidence: 99%
“…Fresh colour, drip loss, shear force, pH 45 min postmortem (pH 45 ), crude protein, and crude fat of breast muscle were measured using previously described methods (Bianchi et al, 2007;Jiang et al, 2007;Tavárez et al, 2011). Meat colour was determined using Chroma Meter CR-410 (Konica Minolta Co. Ltd., Osaka, Japan) to assess CIE LAB values.…”
Section: Measurement Of Meat Qualitymentioning
confidence: 99%